Onyx extrusion through the scalp after embolization of dural arteriovenous fistula. (31st July 2015) - Singla, Amit; Fargen, Kyle Michael; Hoh, Brian
Abstract : A man in his sixties referred with symptoms of episodic left lip numbness and left arm weakness was diagnosed with a Borden type 3 dural arteriovenous fistula (DAVF) on DSA. Successful Onyx embolization of the DAVF was performed via the distal left occipital artery using an ev3 Apollo detachable tip microcatheter. He underwent surgical obliteration for the residual DAVF 3 days later. Three months later during a routine postoperative clinic visit, the patient produced a plastic bag containing multiple small pieces of Onyx cast and the detached tip of the Apollo microcatheter that had extruded out from his scalp through small spontaneous holes about 5 weeks after the embolization procedure. This spontaneous extrusion of Onyx can be alarming to the patient not expecting it; however, prior knowledge and discussion can lessen the anxiety of both the treating physician and the patient dealing with such a situation.